Application of biomaterials in the eradication of Helicobacter pylori: A bibliometric analysis and overview - Shu, Chunxi; Xu, Zhou; He, Cong; Xu, Xinbo; Zhou, Yanan; Cai, Baihui; Zhu, Yin (Frontiers in Microbiology, 2023)
Helicobacter pylori (H. pylori) is a prominent cause of gastritis, peptic ulcer, and gastric cancer. It is naturally colonized on the surface of the mucus layer and mucosal epithelial cells of the gastric sinus, surrounded not only by mucus layer with high viscosity that prevents the contact of drug molecules with bacteria but also by multitudinous gastric acid and pepsin, inactivating the antibacterial drug. With high-performance biocompatibility and biological specificity, biomaterials emerge as promising prospects closely associated with H. pylori eradication recently. Aiming to thoroughly summarize the progressing research in this field, we have screened 101 publications from the web of science database and then a bibliometric investigation was performed on the research trends of the application of biomaterials in eradicating H. pylori over the last decade utilizing VOSviewer and CiteSpace to establish the relationship between the publications, countries, institutions, authors, and most relevant topics. Keyword analysis illustrates biomaterials including nanoparticles (NPs), metallic materials, liposomes, and polymers are employed most frequently. Depending on their constituent materials and characterized structures, biomaterials exhibit diverse prospects in eradicating H. pylori regarding extending drug delivery time, avoiding drug inactivation, target response, and addressing drug resistance. Furthermore, we overviewed the challenges and forthcoming research perspective of high-performance biomaterials in H. pylori eradication based on recent studies.